Interest of carbohydrate consumption during endurance exercise: a systematic review of systematic and meta-analyses of RCTs - Tarrit, B.; Moretton, C.; Duclos, M.; Metz, L.; Chanseaume-Bussiere, E.; Ennequin, G.; Thivel, D.; Rannou, F. (The Journal of Sports Medicine and Physical Fitness, 2026)
INTRODUCTION: Systematic reviews (SR) and meta-analyses (MA) of randomized controlled trials (RCTs) have reported the benefits of carbohydrate (CHO) consumption in various endurance athletes, mainly cyclists or runners. Gathering existing reviews, the present systematic review tends to determine the best conditions and characteristics of this CHO ingestion to optimize athletes` performance.